2014
DOI: 10.18632/oncotarget.1706
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of the combination of an HSP90 inhibitor and a PI3K/mTOR dual inhibitor against cholangiocarcinoma

Abstract: The PI3K/Akt/mTOR pathway is overactivated and heat shock protein (HSP) 90 is overexpressed in common cancers. We hypothesized that targeting both pathways can kill intrahepatic cholangiocarcinoma (CCA) cells. HSP90 and PTEN protein expression was evaluated by immunohistochemical staining of samples from 78 patients with intrahepatic CCA. CCA cell lines and a thioacetamide (TAA)-induced CCA animal model were treated with NVP-AUY922 (an HSP90 inhibitor) and NVP-BEZ235 (a PI3K/mTOR inhibitor) alone or in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 52 publications
3
45
0
1
Order By: Relevance
“…Inhibition of mTOR signaling may prevent CSC self-renewal and circumvent CSC-mediated resistance to cancer therapeutics [23]. Previous studies have demonstrated that mTOR inhibitor, combined with other antitumor agents or not, could inhibit the development of CCA [28, 29, 34, 35]. ZEB1 silencing, either chemically or by RNAi, in mesenchymal-like cells results in a partial epithelial metaplasia and drug sensitivity [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mTOR signaling may prevent CSC self-renewal and circumvent CSC-mediated resistance to cancer therapeutics [23]. Previous studies have demonstrated that mTOR inhibitor, combined with other antitumor agents or not, could inhibit the development of CCA [28, 29, 34, 35]. ZEB1 silencing, either chemically or by RNAi, in mesenchymal-like cells results in a partial epithelial metaplasia and drug sensitivity [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…[22] In line with this, co-administration of phosphoinositide 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) inhibitor, NVP-BEZ235, with HSP90 inhibitor, NVP-AUY922, synergistically increases apoptosis in both cholangiocarcinoma cells and thioacetamide-induced cholangiocarcinoma animal model. [23] Consistently, Saturno et al investigated the effect of HSP90 inhibitor on TNF-related apoptosis-inducing ligand (TRAIL) resistance in colorectal cancer. They showed that co-treatment of TRAIL with HSP90 inhibitor, 17-AAG, considerably increases apoptosis as compared with a single treatment group in TRAIL-resistant xenograft models of human colorectal cancer.…”
Section: Gastricmentioning
confidence: 99%
“…Intrahepatic CCA, like most other human cancers, commonly shows increased activation of members of the AKT-PTEN-PI3KCA-mTOR pathway, an increase often caused by inactivation of PTEN [76][77][78] . Independent of PTEN expression, levels of phosphorylated AKT or mTOR have been suggested to be prognostic markers associated with good outcome in iCCA [79] .…”
Section: Downstream Of the Erbb Receptorsmentioning
confidence: 99%
“…Independent of PTEN expression, levels of phosphorylated AKT or mTOR have been suggested to be prognostic markers associated with good outcome in iCCA [79] . In fact, attempts to target this pathway either using a PI3K inhibitor (NVP-BEZ235) alone [76,77] or in combination with the selective HSP90 inhibitor (NVP-AUY922) [76] have demonstrated promising anticancer activity [77] as well as increased oxidative and ER stress [76] .…”
Section: Downstream Of the Erbb Receptorsmentioning
confidence: 99%